What are the challenges and barriers for the entrepreneurship ecosystem in the Iranian health system?: A qualitative research - Nahid Jamali; Sayed M. H. Emami; Soudabeh Vatankhah; Mohammad R. Maleki (Journal of Education and Health Promotion)
BACKGROUND: In the era of globalization, sustainable development is imperative for health and well-being of fellow citizens. With the available human resources and infrastructure, the Iranian heath system should provide a tremendous scope to contribute to the nation’s health economy. We need to identify and rectify the flows of our health economy. The thrust of this paper was to discover the challenges and barriers of achieving an entrepreneurial ecosystem in Iran’s health sector. MATERIALS AND METHODS: The study objectives and qualitative method allowed to conduct focus group interviews with 16 entrepreneurs, policy makers, operational executive directors, and researchers affiliated to public and private health sectors. Data were computer-analyzed using Max QDA 2020 software, yielding 4 categories, 10 subcategories, and 60 conceptual codes (challenges) revolving around 6 dimensions of Eisenberg’s entrepreneurship ecosystem (financing, politics, human capital, culture, market, infrastructure, and support). The validity and reliability of the results were evaluated and confirmed by matching the homogeneity of the findings. RESULTS: The participants enumerated 60 challenges in 4 major fields including policies, structural-organizational processes, implementers’ characteristics, and prevailing context and conditions based on Eisenberg’s ecosystem dimensions. The challenges are listed in order of importance as follows: the weaknesses in infrastructure and support systems, sociocultural elements, human capital, market, financing, and current health policies. CONCLUSION: Sixty barriers and challenges are found and listed in order of frequency and importance and categorized in six Eisenberg’s dimensions of ecosystem. Weaknesses in infrastructures, support system, and sociocultural elements are the most important barriers toward development.